Incidence of Thrombocytopenia in Pregnant Females - Dilawar, Amna; Taj, Nergis; Afzal, Muhammad; Zubair, Zainab; Naseem, Saira (Journal of Neonatal Surgery, 2025)
Background: Thrombocytopenia is a common hematologic disorder in pregnancy, posing potential risks of maternal and fetal complications. Routine monitoring can aid in early detection, yet factors associated with thrombocytopenia in pregnancy remain underexplored. Objective: This study aimed to determine the frequency of thrombocytopenia in pregnant women and assess its association with demographic and clinical factors, including maternal age, gestational age, parity, hypertension, and diabetes mellitus. Material and Methods: A descriptive, cross-sectional study was conducted at the Islamgarh Welfare Trust Hospital, Islamgarh Mirpur Azad Kashmir, over six months (March 2024 to September 2024). A sample size of 222 pregnant women was calculated based on a 17.5% expected frequency of thrombocytopenia, with a 95% confidence level and 5% margin of error. Non-probability consecutive sampling was employed. Data collection included sociodemographic and clinical variables. Blood samples were analyzed for platelet count, defining thrombocytopenia as <150,000/µL. Chi-square tests were used to assess associations, with a p-value ≤0.05 considered statistically significant. Results: Thrombocytopenia was identified in 30.2% (n=67) of the participants, while 69.8% (n=155) did not exhibit thrombocytopenia. No statistically significant associations were observed between thrombocytopenia and maternal age (p=0.340), gestational age (p=0.303), parity (p=0.303), hypertension (p=0.406), or diabetes mellitus (p=0.948). These findings suggest that thrombocytopenia in pregnancy may frequently occur independently of these factors. Conclusion: Thrombocytopenia affected a significant portion of this sample population. Although not significantly associated with the studied factors, routine platelet monitoring in pregnancy remains essential for early detection and management